Visionary Leadership and Digital Transformation: Driving the Sustainability of Islamic Primary Education - Nikmatul Sholihah; Edi Kurniawan Farid; Yeniati Ulfah (Al-Qalam Institue, 2026)
This study aims to analyze visionary leadership in enhancing madrasah sustainability in the digital era. The research employed a qualitative case study approach, utilizing interviews, observations, and documentation as data collection techniques. Data were analyzed through a cyclical process consisting of data reduction, data display, and conclusion drawing. The findings reveal that Madrasah Ibtidaiyah Sunan Ampel has successfully developed an educational vision aligned with advancements in digital technology and has actively improved teachers’ digital competencies through continuous professional development programs. The empowerment of digital educational resources has also been carried out through the provision of hardware, as well as access to online learning applications and platforms. Furthermore, the integration of technology into the learning process has enhanced both interactivity and flexibility. However, challenges remain regarding the availability of comprehensive digital learning materials, particularly for Islamic Religious Education subjects. This study contributes to the growing body of literature on technology integration in Islamic education and provides insights for educational leaders and policymakers on leveraging technology more effectively to improve learning quality in the digital era.